PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA PT KISEL (ANAK PERUSAHAAN PT TELKOMSEL) MEDAN - Muhammad Yamin Siregar; Intan Wahyu Ningsih (Universitas Medan Area, 2016)
The objective of this research is to determine the impact of service quality dimension viewed from tangible, reliability, responsiveness, assurance, and empathy dimension towards customer satisfaction at PT. Kisel (Official Branch of PT. Telkomsel) Medan.In this research the population’s 103 respondent with sample’s used is 82 respondent. The sample selection method used is purposive sampling, based on Telkomsel customer that visit PT Kisel to complaint their problem more than 1 time. Data analyzing method that is used is multiple linear regression using SPSS version 19.0 program.The result of this research is tangible, reliability, responsiveness, assurance, empathy simultaneously have positive and significant influencetoward customer satisfaction. Based on test only reliability variable and assurance have significant influence towards customer satisfaction. based on coefficient determination test ( R2) 86,3% of customer satisfaction can be explained by tangible, reliability, responsiveness, assurance, and empathy, while the rest 13,7% is explained by other variables not observed in this research.Keywords :Tangible, Reliability, Responsiveness, Empathy, Customer satisfaction